2019
DOI: 10.1080/02701367.2019.1612511
|View full text |Cite
|
Sign up to set email alerts
|

How Does the Adjustment of Training Task Difficulty Level Influence Tactical Behavior in Soccer?

Abstract: Purpose: This study aimed to investigate if player tactical skill level and age category influence team performance and player exploratory behavior in tasks with different difficulty levels. Method: In total, 48 youth male soccer players participated in the study (U15, n = 24, mean age = 13.06 ± 1.53 years; U17, n = 24, mean age = 16.89 ± 0.11 years). Player tactical skills were evaluated through the System of Tactical Assessment in Soccer (FUT-SAT), allowing them to be organized into three groups according to… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
44
1
10

Year Published

2020
2020
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 45 publications
(59 citation statements)
references
References 27 publications
(41 reference statements)
2
44
1
10
Order By: Relevance
“…A description of the four included studies can be found in Table 3. In the included studies, one was focused on visual searching strategies [43], one on verbalized knowledge [46], and five of them on movement and response accuracy [25,40,44,45,47].…”
Section: Comparisons Between Different Age Groupsmentioning
confidence: 99%
See 2 more Smart Citations
“…A description of the four included studies can be found in Table 3. In the included studies, one was focused on visual searching strategies [43], one on verbalized knowledge [46], and five of them on movement and response accuracy [25,40,44,45,47].…”
Section: Comparisons Between Different Age Groupsmentioning
confidence: 99%
“…Other actions beyond declarative and execution of technical actions were compared between age groups. In the included studies, Machado et al [45] and Gonçalves et al [44] compared the tactical knowledge and behaviors of youth football players from different age groups. Machado et al [45] identified the tactical skill levels of under-15 and under-17 players using System of Tactical Assessment in Soccer (FUT-SAT) during G+3 vs. 3+GK games.…”
Section: Comparisons Between Age Groupsmentioning
confidence: 99%
See 1 more Smart Citation
“…A study that tested the effects of maturation on tactical efficacy [16] highlighted that maturation and proficiency of peripheral perception (important contributor to making decisions) may justify a better identification of the teammates in a timely position to receive the ball, assertively predict the movements of the teammates and improve searches for new information without central vision. Moreover, the effects of accumulated experience and tactical efficacy (as discriminator of expertise) may lead to changes in exploratory behaviors of players [17]. In a study conducted on youth football players it was possible to observe that youth players with better tactical skill levels and older-age groups presented greater exploratory behaviors in games [17].…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, the effects of accumulated experience and tactical efficacy (as discriminator of expertise) may lead to changes in exploratory behaviors of players [17]. In a study conducted on youth football players it was possible to observe that youth players with better tactical skill levels and older-age groups presented greater exploratory behaviors in games [17]. Thus, there are reasons to hypothesize that collective dynamics can be affected by age, maturation and expertise level.…”
Section: Introductionmentioning
confidence: 99%